Pengembangan Buku Panduan Badan Usaha Milik Rukun Tetangga (BUMRT) Untuk Meningkatkan Daya Saing Usaha Mikro - Prabowo, Andri Eko; Azmansyah, Azmansyah; Baskara, Agus; Salma, Tiara; Lestari, Tria Fuji (Jurnal Pendidikan Ekonomi (JUPE), 2024)
A large number of micro preneur in Indonesia have difficulties in developing their businesses. This research aims to develop a guidebook for the establishment of BUMRT to improve the competitiveness of micro enterprises. The development model carried out in this study is the ADDIE model. The development results were tested on micro businesses in Dusun III Bendah Pudu, Kampar Regency. The trial results showed that the BUMRT guidebook was able to improve students' understanding of the merger strategy to improve business competitiveness. The results also showed that the BUMRT guidebook was suitable for use by the community.